PENDIDIKAN KEPRAMUKAAN SEBAGAI WAHANA PEMBENTUK KARAKTER DAN EKSTRAKURIKULER WAJIB BAGI SISWA SEKOLAH MENENGAH ATAS BERDASARKAN KURIKULUM 2013 (STUDI KASUS SMA NEGERI 1 BATUSANGKAR) - emil da (FKIP UMSB, 2017)
World Education today face many complex issues and needs to be addressed. One indicator of the cause is the curriculum that is always changing, so the schools are less ready for implementation, state teachers are less qualified in terms of competence education, school facilities is incomplete, and the most crucial issue of student, where there is an imbalance between the development of intellectual emotional. This resulted in the decline in manners of social and moral ethics in the practice of school life, causing a number of adverse effects are troubling the public, such as less behave respectful to teachers and employees, no concern, they are often late to class, ditching, do not wear uniforms with full and wear clothes that do not fit the model of school regulations, brawl between students, smoke, do immoral and others. Even student misbehavior tends to the category of criminal acts such as theft, drug abuse and murder. which is generally referred to as crimes of students. This study aimed to describe extracurricular scouting compulsory education as a vehicle for forming the character of students SMA Negeri 1 Batusangkar. Types and methods used in this research is a field research using qualitative methods. Subjects of this study as many as 11 people, consisting of Waka Kesiswaan, Scoutmaster (5 people) and the Council of shelves (5 people). Data collection techniques used in this study is a questionnaire, observation and documentation. As for analyzing qualitative descriptive technique used, including: data reduction, data presentation, and conclusion or verification. Based on the analysis of data that scouting education compulsory extracurricular activities in SMA Negeri 1 Batusangkar, already implementing the values of the characters and already implemented in accordance with the purpose of the scout movement. In addition, scout curriculum used at extracurricular education compulsory scouting SMA Negeri 1 Batusangkar, referring to the educational curriculum scouting conceived and established by Kwarnas Scout Movement. The provision is contained in the AD/ART scout movement. It can be concluded that the compulsory extracurricular scouting education as a vehicle for forming the character of students at SMA Negeri 1 Batusangkar can be said to have been effective. Overall education compulsory extracurricular activities of scouting in SMA Negeri 1 Batusangkar already implementing character values listed on the purpose of the scout movement, the basic principles and methods of scouting, as well as the practice Trisatya and Dasadarma in each activity.Keywords: Education scouting, character.